THE BOYCOTT OF ISRAELI PRODUCTS FROM THE PERSPECTIVE OF SADZ AL-DZARAI’: A NORMATIVE ANALYSIS WITHIN ISLAMIC LAW - Fauziah, Ai Samrotul (Universitas Nurul Jadid, 2025)
The phenomenon of boycotting Israeli products in Indonesia is a form of showing the morality and conscience of society based on very serious solidarity with Palestine. The boycott was carried out due to genocide and intimidation carried out by Israel, especially Israeli attacks which have recently increased and become more severe in most of the Palestinian territories. The context of this discussion is the Boycott, Divestment, Sanctions (BDS) movement which was born as the key to suppressing various large companies that have ties to Israel and support their economic prosperity. This was done with the intention of supporting the Palestinian people who have been sadistically and horribly oppressed. This research was conducted with the aim of analyzing the phenomenon of boycotting Israeli goods from the perspective of sadd adzzariyat. This research uses descriptive qualitative by analyzing secondary data from various literature sources, including case studies, scientific journals and articles. This research will discuss the phenomenon of boycotting as viewed from sadd adzzariyat, as Islamic law studied by Ushul Fiqh scholars explains that sadd adzzariyat prohibits or prevents work that was previously permissible to be done but can lead to something that is prohibited.